Khamr Drinking From An Islamic Perspective: A Sociological Case Study On Malaysian Malay Males - Majid, Nik Suhaida Nik Abdul (2020)
This is a sociological study about the practice of khamr drinking among 12 Malaysian Malay male informants from different social classes. It analysed the reasons that caused these Malays to drink by examining their social background. It highlighted the role of social agents in influencing their socialisation process, hence leading them to be deviant from the Islamic viewpoint. This viewpoint is selected as the basic framework which concerns the concepts of ‘aqīdah, sharī‘ah, and akhlāq since Malays, being Muslims are prohibited to drink khamr. Therefore, by consolidating revealed knowledge and empirical data, this research provides a unique discourse to the topic of khamr drinking. Being a qualitative case study, data were collected through snowball and purposive sampling and analysed by using narrative and interpretive biography. Interview was conducted in Negeri Sembilan, Selangor, and Kuala Lumpur. Findings reveal that the drinking habit is different in every social class. However, the informants share similar beliefs about drinking khamr. They knew that khamr is prohibited in Islamic teaching but not clearly understand the concept of prohibition, thus leading them to be drinkers. Furthermore, it was found that shaiṭān is the main dominating factors besides social agents such as family, peer group and government for drinking among the informants.